Nurses' perceptions and experiences regarding Morphine usage in burn pain management. Issue 4 (June 2015) - Bayuo, J.; Agbenorku, P.
Abstract Introduction Morphine, a classical example of opioid has been described as one of the analgesics of choice for burn pain management but there have been reports of under utilization of the medication and subsequent poor pain management. Nurses have a pivotal role in successful burn pain management and should therefore possess positive perception as well as strong knowledge base of pain care. Aim In light of this realization, this study sought to investigate the perception and experiences of nurses working in the burns unit possess towards the medication. Methodology Purposive sampling approach was used to select twenty (20) nurses. Descriptive and themed content analysis approaches were used to analyze data. Results Mean years in general nursing practice and practice in the burns unit were obtained as 7.4 and 3.4 years respectively. Results indicate that nurses have a clear understanding of the intensity of burn pain but perception towards morphine was mixed and some respondents were unsure about some of the pertinent facts of morphine and thus, would prefer other medications such as paracetamol, diclofenac and pethidine. Addiction to the medication and morphine causing death were major themes identified. Conclusion The resultant effect of these perception and experiences imply and confirm the under usage of morphine. It is therefore recommended that nurses within the burn unit be taken through training modules on the suitability of morphine in burn pain management.